Analysis of survival-skills among adolescents in Yogyakarta - Enik Nurkholidah; Syamsu Yusuf; Ilfiandra Ilfiandra; Ahman Ahman (Jurnal Konseling dan Pendidikan, 2022)
The survival-skills are important to be possesed by adolescents. Nowadays, the threats in their environment are increasing and having survival-skill would help them to cope with problem that they face. Unfortunately, empirical study on survival-skills are rarely conducted. The purpose of this study is to examine and obtain an empirical picture of adolescent survival-safety skills in Yogyakarta. The research method that has been applied is a survey of 312 adolescents in 5 schools in Yogyakarta. The conclusion of this study is an affirmation of the findings of the findings as well as answers to the research questions that adolescents in Yogyakarta are generally in the potential of Survival-Safety Skills in the Medium category, meaning that conditions are sufficient to survive safely and obtain a sense of security for adolescents in living a life more prosperous. However, in some aspects it still shows Low, especially on Aspects: psychospiritual, Environmental Adaptation, and Having Hope